KRESNA GUGAT DALAM PERTUNJUKAN WAYANG KULIT PURWA GAYA SURAKARTA - M. Randyo (Institut Seni Indonesia Surakarta, 2013)
Kresna Gugat (Krishna sues) play is one of carangan leather puppet performance contains valueof justice. The main character in the plays has the character of a wise and determine the course ofthe next play. Krishna in his young likes to study to many Begawan /experts have an eyesight assharp as gods. Krishna in Kresna Gugat Play is a symbol that represents a range characters whokeep the world. The problem of this study is namely how is the structure of scene play and itssymbolic significance. The analysis showed that in the world there is a treatment that is less fair,which will make a destructive to the nature. Due to the lack of fair , unwise, there was negligence ofruler world namely Guru Dewa. The symbolic behavior that let Sela Mustaka, the king of MelasaPurathat is reign in border forest Trajutrisna means underestimates the power of Undraprasta led byPunta Dewa. The king of Melasa Pura is an enemy who infiltrated the border of Indraprasta andDwarawati that cause conflict. The tragedy of power struggle between Indraprasta and MelasaPura interesting to be revealed because of Krishna. The result belong to Pandawa who are knight,symbol of justice and dedication to help re settle Indraprasta from enemy interference. ThroughKresna Gugat the peace of the world can be sued because of the false and mistake from theleader.